2010
DOI: 10.1158/1078-0432.ccr-10-2363
|View full text |Cite|
|
Sign up to set email alerts
|

Bevacizumab plus Fotemustine as First-line Treatment in Metastatic Melanoma Patients: Clinical Activity and Modulation of Angiogenesis and Lymphangiogenesis Factors

Abstract: We report on experiences at the Software Sustainability Institute (SSI) in customizing and using the Trac system to provide a single platform for recording, managing and tracking a wide range of community interactions. We note the essential requirement of a lightweight, easy-to-use system for recording 'community metadata' and discuss the pros and cons of using Trac in this way for day-to-day operations within SSI, and more generally as a means to record and track interactions with a wide and potentially very … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Recently Del Vecchio [133] investigated the modulation of bevacizumab administration in metastatic melanoma patients and evaluated the angiogenesis modulation. This study showed that serum VEGF-A and overall proangiogenic activity were significantly inhibited.…”
Section: Predictive Markers and New Drugsmentioning
confidence: 99%
“…Recently Del Vecchio [133] investigated the modulation of bevacizumab administration in metastatic melanoma patients and evaluated the angiogenesis modulation. This study showed that serum VEGF-A and overall proangiogenic activity were significantly inhibited.…”
Section: Predictive Markers and New Drugsmentioning
confidence: 99%
“…All serum samples were evaluated in duplicate. Briefly, sera from the patients and controls were incubated with biotinylated antibodies as described previously (36). Next, streptavidin-horseradish peroxidase (SA-HRP) was added.…”
Section: Serum Biomarker Analysismentioning
confidence: 99%
“…In addition, this study also investigated a variety of predictive biomarkers, including (i) ERK and AKT phosphorylation in peripheral blood lymphocytes (PBL; refs. [33][34][35] and (ii) serum levels of cytokines involved in angiogenesis and lymphangiogenesis (36).…”
Section: Introductionmentioning
confidence: 99%
“…Phase II studies have shown some activity against melanoma in combination with IFN and fotmustine. 13 A large Phase III study is ongoing to assess efficacy of response to therapy with bevacizumab in the adjuvant setting for surgically resected advanced disease (AVAST-M study).…”
Section: Antibodies Targeting Vascular Endothelial Growth Factormentioning
confidence: 99%